Perpetual and Virtual Patients for Cardiorespiratory Physiological Studies - Brossier, David; Sauthier, Michael; Alacoque, Xavier; Masse, Benoit; Eltaani, Redha; Guillois, Bernard; Jouvet, Philippe (Journal of Pediatric Intensive Care, 2016)
As a result of innovations in informatics over the last decades, physiologic models elaborated in the second half of the 20th century could be transformed into specific virtual patients called computational models. These models, developed initially for teaching purposes, are of great potential interest in responding to current concerns about improving patient care and safety. However, even if there are obvious advantages to using computational models in cardiorespiratory management, major concerns persist as to their reliability and their ability to recreate real patient physiologic evolution over time. Once developed, these models require complex validation and configuration phases prior to implementation in daily practice. This article focuses on the development of computational models, and reviews the methodologies to clinically validate the models including specific patient databases (perpetual patients) and the use in clinical practice including very high fidelity simulation.
Keywords: children; intensive care; modeling; cardiorespiratory physiology; simulation; databases